Lithium dilution in Li-Sn alloys. (December 2020) - Mateus, R.; Costa, M.B.; Alves, L.C.; Guedes, M.; Alves, E.; Ferro, A.C.
Highlights: 50 at.% Li-Sn blend produced by high energy ball milling of pure Li and Sn at RT. SEM analysis showed the thin cluster morphology of the blend. Intermetallics with lowest Tm identified by XRD after annealing at 160 °C over 2 h. Dilution of the blend with pure Sn to achieve final 5 at.% and 1 at.% Li contents. Good elemental homogeneity and purity of the diluted alloys revealed by IBA. Abstract: Liquid lithium-tin (Li-Sn) alloys are being considered in alternative concepts of plasma facing components for nuclear fusion applications. Nevertheless, the high Li content and high melting temperature of Li-rich intermetallics may hinder their use due to a possible excessive evaporation of Li to the vessel with evident issues in fuel retention. Their formation was inhibited in this study in homogeneous alloys with Li contents as higher as 5 at.% via a mechanical alloying route of pure Li and Sn sources. A 50 at.% Li-Sn master powder was initially prepared and diluted afterwards with pure Sn to achieve the final compositions. The structure, elemental composition and homogeneity of the alloys were assessed by scanning electron microscopy, ion beam analysis and X-ray diffraction. 5 at.% Li and 1 at.% Li alloys composed by phases with low melting temperatures, LiSn, Li2 Sn5 and β-Sn, mainly, were produced with reduced oxygen and metallic impurity contents.